Teachers’ Beliefs : Kompetensi Emosional dan Sosialisasi Emosi pada Anak Usia Dini - Mafaza Mafaza; Septi Mayang Sarry (Jurnal Ilmu Perilaku, 2023)
Teachers' beliefs about emotions can provide an overview of how teachers support the development of emotional competence in early childhood. This study aimed to investigate preschool teachers’ beliefs about emotional competence and emotion socialization. A sample of 194 preschool teachers from 22 Kindergartens completed the Teachers' Emotion Beliefs Scale (TEBS) and open questionnaires. The data were analyzed using descriptive statistical techniques and thematic analysis. The research results showed that 67% of teachers had developmentally appropriate beliefs, while 33% of teachers had beliefs that were not appropriate to children's emotional development. The developmentally appropriate belief explains the importance of the teacher's role in facilitating children's emotional competence. On the other hand, unappropriateness is explained by teachers' beliefs regarding children's expressions of negative emotions (such as sadness and anger), which according to teachers, young children do not need to express these emotions for certain reasons. Furthermore, the results of the open-ended questionnaire showed several teacher limitations regarding conceptual understanding of children's emotional competence, as well as in using appropriate strategies for emotional socialization (especially in helping children manage negative emotions). The way teachers socialize emotions is based on their beliefs regarding children's emotional competence.